2022
DOI: 10.1021/acsami.2c11162
|View full text |Cite
|
Sign up to set email alerts
|

Large Spin-To-Charge Conversion at the Two-Dimensional Interface of Transition-Metal Dichalcogenides and Permalloy

Abstract: Spin-to-charge conversion is an essential requirement for the implementation of spintronic devices. Recently, monolayers of semiconducting transition metal dichalcogenides (TMDs) have attracted considerable interest for spin-to-charge conversion due to their high spin-orbit coupling and lack of inversion symmetry in their crystal structure. However, reports of direct measurement of spin-to-charge conversion at TMD-based interfaces are very much limited. Here, we report on the room temperature observation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 69 publications
4
21
1
Order By: Relevance
“…69,72,73 A similar phenomenon i.e., complete spin angular momentum relaxation in MLs for TMDs was also reported in previous reports. [15][16][17] This ISOC is also well known to provide the most dominating role in spin relaxation for 2D NM materials. [74][75][76][77] However, in the case of 3D NMs such as HMs (Pt, W, Ta, and so on), the spin relaxation occurs in the bulk of the HM layer via symmetry independent bulk SOC and has exponential dependence on the NM material thickness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…69,72,73 A similar phenomenon i.e., complete spin angular momentum relaxation in MLs for TMDs was also reported in previous reports. [15][16][17] This ISOC is also well known to provide the most dominating role in spin relaxation for 2D NM materials. [74][75][76][77] However, in the case of 3D NMs such as HMs (Pt, W, Ta, and so on), the spin relaxation occurs in the bulk of the HM layer via symmetry independent bulk SOC and has exponential dependence on the NM material thickness.…”
Section: Resultsmentioning
confidence: 99%
“…It is experimentally demonstrated that the monolayer of MoS 2 has the potential to become a good spin sink material when used with Co, 14 Co 2 FeAl, 15 Co 2 FeSi 16 and Ni 81 Fe 19 . 17,18 However, its compatibility with other potential FMs is yet to be explored. These properties of TMDs are essential for exploring new spin-based physics and developing energy-efficient ultrafast future spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4a shows a representative ISHE signal, V ISHE (open circles) along with an ISHE signal measured from a Ta/Py/SiO 2 sample (inset). To eliminate contribution from self-induced ISHE and other rectification effects from Ni 80 Fe 20 , [32][33][34] the signal from a reference (Ni 80 Fe 20 ) sample is subtracted from the measured data (refer to Section S2, Supporting Information, for more details). The sign of signal obtained from Mn 3 Sn agrees with Ta, indicating a negative sign of 𝜃 SH .…”
Section: Resultsmentioning
confidence: 99%
“…From this, we determine spin mixing conductance to be ∼7.6 × 10 19 m −2 , which is higher than those ofother TMD/ NiFe systems. 16,17 The lower value of α for d PtSed 2 = 5 nm is attributed to the lower van der Waals interaction observed in Raman measurements (see section S5 in the Supporting Information) for this sample. The inhomogeneous line width ΔH 0 is found to be similar for all the devices, ∼5 ± 3 Oe, indicating no significant degradation in the quality of the magnetic layer (NiFe) grown on PtSe 2 .…”
mentioning
confidence: 89%
“…Significant efforts have been reported to improve the energy efficiency of HM-based SOT devices. One method to achieve a higher SOT efficiency is to replace the HM layer with alternative materials that have a large charge-to-spin conversion efficiency and high conductivity. Transition metal dichalcogenides (TMDs) are potential replacements of HM due to various properties such as tunable conductivity, , high spin–orbit coupling, the presence of Dzyaloshinskii–Moriya interaction, tunable band structure, , spin-layer locking, and long spin lifetime . The use of TMDs in SOT devices has shown a number of advantages, e.g., the ability to control SOT using the crystal symmetry and electric field …”
mentioning
confidence: 99%